A Study On Cultivating Learning Culture As A Strategy For Organizational Success - Premi, Harish; Pahwa, Mohit (Gyan Management Journal, 2020)
Success is a subjective and comprehensive concept and so is the learning. This paper is aimed at studying the importance of learning culture and to identify the drivers to cultivate learning culture and further to develop a conceptual framework as a strategy for Organization Success. Today’s business environment is becoming more and more dynamic and complex impacted by various factors such as rapid change in technology, creative destruction and reinvention. The fast paced technology is affecting every industry and area of life, and work is no exception to this. To become successful in changing times, work must become more meaningful and must include constant learning. An organization learning culture is referred to ‘a set of norms and values that define the functioning of an organization which motivates individuals as well as the organization for continuous learning’. The present study aims to indentify the variables that affect the learning culture in an organization. Based on the literature review and subsequent study, six main independent variables are indentified i.e. growth oriented mindset, lead by example, reflective mindset, test-and-learn culture, feedback and reward mechanism, while the mediating variables are increased job satisfaction, lower turnover rates, increased profitability, profits and flexibility and ‘Organization Success’ is taken as the dependent variable. This study is significant for an organization to indentify the most valuable driver that can contribute to cultivate a learning culture as a strategy. After all, it’s the learning of each and every individual which helps an organization to grow not only in terms of physical resources but also in terms of intellectual capabilities which is the only fundamental requirement to achieve the success in real terms.